STUDY OF GROWTH AND SURVIVAL OF CLIMBING PERCH (ANABAS TESTUDINEUS BLOCH) WITH DIFFERENT SEX RATIO IN BIOFLOC SYSTEM - Hanafie A.; Biyatmoko D.; Fatmawati; Fauzana N.A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
The purpose of this research was to analyze how the performance of growth and survival of climbing perch - papuyu fish (Anabas testudineus Bloch) aquaculture with the biofloc system whether there were differences in the sex ratio of the stocked climbing perch had an effect and to find the right sex ratio. The experimental design used in this research was a completely randomized design (CRD) with 5 treatments and 5 replications, resulting in 25 experimental units. Treatment B100J0 = 100% female climbing perch and 0% male, treatment B75J25 = 75% female and 25% male climbing perch, treatment B50J50 = 50% female and 50% male climbing perch, treatment B25J75 = 25% female climbing perch and 75% male % and Treatment B0J100 = 0% female climbing perch and 100% male fish. The research was conducted for 90 days with daily growth parameters (SGR), weight and length growth, survival rate, food conversion, flock content, and main water quality parameters (water temperature, pH, dissolved oxygen and dissolved ammonia). From the results of the research it can be concluded that the difference in sex ratio has a significant effect on the weight growth of climbing perch with a 100% ratio of females for enlargement resulting in the best daily growth rate. The B100J0 treatment was better, that in subset 1 the treatments B0J100, B75J27 and B50J50 were the same. In subset 2, treatments B50J50 and B75J25 were the same, while in subset 3, treatments B75J25 and B0J100 had the same growth. However, based on the median value, treatment B100J0 was better than treatments B75J25 and B50J50 and other treatments. The difference in relative weight (%) between treatments indicates that treatment B100J0 23.72% from treatment B75J25, 54.57% from treatment B50J50, 86.39% from treatment B25J75 and 172.87% from the B0J100 treatment. thus treatment B100J0 = 100% female and 0% male is the best treatment. This phenomenon indicates the sex of the papuyu fish with a ratio of 100% female to rearing produces the best daily growth rate. The results of the research using the sex composition obtained an additional length (cm) for 90 days for each treatment B100J0 = 1.92 cm, B75J25 = 1.19 cm, B500J50 = 1.78 cm, B25J75 = 1.31, B0J100 = 1.61 cm, indicating length The standard depends on the other types of climbing perch, the variety of fish species tested and the length of time they are kept. Treatments B0J100, B75J25 and B50J50 had the same survival in subset 1, while in subset 2 treatments B100J0 and B75J25 had the same survival. Sex ratio was significantly different between treatments to food conversion. Then the Post Hoc test was carried out, the results of the analysis showed that the B100J0, B75J25, B50J50 and B25J75 treatments in subset 1 were just as good in their food conversion. Whereas in subset 2 the B0J100 treatment was not the same as the other four treatments. Floc content ml/L. Rangeflocs of all treatments within the range of 9.583-10.524 ml/L, were able to contribute in providing food in the rearing medium. The water temperature during the research period, air and water temperatures ranged from 26.89-27.62 °C (ºC). From the results of this research the range of acidity degrees in all treatments was in the range of 6.87-7.04. The DO concentration at the experimental site ranged 5.1-7.8 mg L-1, which is within the acceptable range for aquaculture.